Innovative financing for a gender-equitable first-food system to mitigate greenhouse gas impacts of commercial milk formula: investing in breastfeeding as a carbon offset - Smith, Julie P.; Borg, Bindi; Iellamo, Alessandro; Nguyen, Tuan T.; Mathisen, Roger (Frontiers in Sustainable Food Systems, 2023)
• Women’s contributions to food production and food security are often overlooked, thus perpetuating inequitable and unsustainable globalised commercial food systems. • Women’s role as producers in the first-food system, breastfeeding, is largely invisible, and underfunded, encouraging the production and consumption of environmentally unsustainable commercial milk formula (CMF). • This policy brief highlights opportunities for including and funding interventions enabling breastfeeding under carbon offset schemes such as the United Nations Clean Development Mechanism (CDM). • A Green Feeding Tool is being developed to account for the national carbon and water footprints of CMF. • The tool will help ensure that women’s contributions to a sustainable ‘first-food system’ is not ignored by the CDM and other mechanisms funding greenhouse gas emissions reductions.